Tribology of hot forming tool and high strength steels - Hardell, Jens (Luleå tekniska universitet, Maskinelement, 2009)
Tribological research pertaining to moving machine components operating at elevated temperatures has so far received only limited attention despite the fact that many technological applications encounter high-temperature conditions. Examples of such applications can be commonly found in the aerospace, power generation and hot metal working industries. In the metal working field, thermo-mechanical forming of high-strength steel components has grown very rapidly in recent years. The increased usage of such components has its driving forces in improved crashworthiness, reduced fuel consumption and conservation of natural resources. These processes, invented about 30 years ago in northern Sweden, enable the forming of complex shaped components at elevated temperatures and the simultaneous control of complex microstructures. Despite the fact that more than 30 years of research has gone into developing and optimising these thermo-mechanical processes there are several aspects which have not been adequately studied or understood. One of these aspects is the tribology of the tool-workpiece interaction at the high temperatures encountered during hot metal forming. This is where tribological research can contribute greatly in improving the hot sheet metal forming processes. The main tasks involved are the understanding, prediction and control of friction as well as wear during the interaction of tool and workpiece at elevated temperature. Future research also needs to consider the tribology of rapidly emerging surface engineering technologies that have potential for high temperature applications such as hot metal forming. This work has focussed on investigating the friction and wear characteristics of different tool steels during sliding against ultra high strength boron steel at different temperatures ranging from room temperature to 900 °C. Tribological studies have also been conducted on surface treated/coated tool steels during sliding against coated workpiece material with a view to explore the potential of surface ...